Oxidative Stress Parameters Can Predict the Response to Erythropoiesis-Stimulating Agents in Myelodysplastic Syndrome Patients - Gonçalves, Ana Cristina; Alves, Raquel; Baldeiras, Inês; Jorge, Joana; Marques, Bárbara; Paiva, Artur; Oliveiros, Bárbara; Cortesão, Emília; Nascimento Costa, José Manuel; Sarmento-Ribeiro, Ana Bela (Frontiers in Cell and Developmental Biology, 2021)
Oxidative stress has been implicated in the development of several types of cancer, including myelodysplastic syndromes (MDS), as well as in the resistance to treatment. This fact leads us to investigate whether oxidative stress parameters were associated with the response to erythropoiesis-stimulating agents (ESAs) in lower-risk MDS patients. To this end, we analyzed the systemic levels of reactive species (peroxides and NO), antioxidant defenses (uric acid, vitamin E, vitamin A, GSH, GSSG, TAS, as well as GPX and GR activities], and oxidative damage (8-OH-dG and MDA) in 66 MDS patients, from those 44 have been treated with ESA. We also calculated the peroxides/TAS and NO/TAS ratios and analyzed the gene expression of levels of the redox regulators, NFE2L2 and KEAP1. We found that patients that respond to ESA treatment showed lower levels of plasma peroxides (p < 0.001), cellular GSH (p < 0.001), and cellular GR activity (p = 0.001) when compared to patients who did not respond to ESA treatment. ESA responders also showed lower levels of peroxides/TAS ratio (p < 0.001) and higher levels of the expression of the NFE2L2 gene (p = 0.001) than those that did not respond to ESA treatment. The levels of plasmatic peroxides shown to be the most accurate biomarker of ESA response, with good sensitivity (80%) and specificity (100%) and is an independent biomarker associated with therapy response. Overall, the present study demonstrated a correlation between oxidative stress levels and the response to ESA treatment in lower-risk MDS patients, with the plasmatic peroxides levels a good predictive biomarker of drug (ESA) response.